Organochlorine pesticides exposure may disturb homocysteine metabolism in pregnant women - Yin, Shengju; Wei, Jing; Wei, Yihui; Jin, Lei; Wang, Linlin; Zhang, Xuejuan; Jia, Xiaoqian; Ren, Aiguo (The Science of the total environment, 2020)
[Display omitted] •Plasma concentrations of certain OCPs were positively correlated with plasma Hcy.•OCPs may disturb the folate-dependent homocysteine metabolic pathway in human body.•Folic acid supplementation may have protective effect against toxicity of certain OCPs. Maternal exposure to organochlorine pesticides (OCPs) has an adverse impact on maternal and fetal health, and excessive homocysteine is related to a variety of adverse pregnancy outcomes. Biomimetic studies suggest that OCPs interfere with folate-dependent pathways, but little evidence is available from studies with human subjects. This study explored whether exposure to OCPs interferes with the metabolism of homocysteine, which is folate dependent. A total of 313 pregnant women at 12–20 weeks gestation were recruited in Shanxi province, China, from 2014 to 2015. Plasma concentrations of 20 OCPs, including dichlorodiphenyltrichloroethane and metabolites (DDTs), hexachlorobenzene (HCB), and hexachlorocyclohexanes (HCHs), were analyzed by gas chromatography–mass spectrometry. Blood folate concentrations were analyzed by microbiological assay, and plasma homocysteine concentrations were determined by enzyme-linked immunosorbent assay. Information on demographics, lifestyle behaviors, and folic acid supplementation was collected by in-person interview. Of the women, 99% reported having taken folic acid supplements. Results of a logistic regression analysis showed that higher plasma levels of OCPs were associated with increased odds of higher plasma homocysteine after adjustment for potential confounding factors. Positive correlations were observed between plasma OCPs and plasma homocysteine concentrations: HCB (r = 0.176, p = 0.002), β-HCH (r = 0.172, p = 0.002), ρ,ρ′-DDE (r = 0.132, p = 0.020), ρ,ρ′-DDD (r = 0.161, p = 0.004), and ο,ρ′-DDT (r = 0.144, p = 0.011). Plasma concentrations of OCPs were negatively correlated with red blood cell (RBC) folate in the low-RBC-folate subgroup, but the correlations were not statistically significant. A positive correlation was observed between OCPs and homocysteine in the low-RBC-folate subgroup. These findings suggest that OCPs may disturb the folate-dependent homocysteine metabolism pathway.